2008
DOI: 10.1002/qj.200
|View full text |Cite
|
Sign up to set email alerts
|

A numerical study of three catastrophic precipitating events over southern France. I: Numerical framework and synoptic ingredients

Abstract: This study examines the simulation of three torrential rain events observed on 13-14 October 1995 (the Cévennes case), 12-13 November 1999 (the Aude case) and 8-9 September 2002 (the Gard case) over the southeastern part of France using the Meso-NH non-hydrostatic mesoscale numerical model. These cases were associated with extreme Heavy Precipitation Events (HPEs) with significant precipitation amounts exceeding 500 mm in less than 24 hours. Several sets of numerical experiments were performed with 10 km and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
238
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 204 publications
(246 citation statements)
references
References 43 publications
3
238
0
4
Order By: Relevance
“…Nuissier et al (2011) found that the synoptic-scale pattern propitious to HPEs over the French Mediterranean region consist of an upper-level trough located over the west of France and an upper-level ridge over central Europe. Nuissier et al (2008) underlined the slow evolution of this synoptic pattern, which is an essential condition to maintain favourable low-level mesoscale conditions for a long enough time.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Nuissier et al (2011) found that the synoptic-scale pattern propitious to HPEs over the French Mediterranean region consist of an upper-level trough located over the west of France and an upper-level ridge over central Europe. Nuissier et al (2008) underlined the slow evolution of this synoptic pattern, which is an essential condition to maintain favourable low-level mesoscale conditions for a long enough time.…”
Section: Introductionmentioning
confidence: 93%
“…Meso-NH has already shown its capability to simulate HPEs in either a real or idealized framework (Ricard, 2005;Nuissier et al, 2008;Ducrocq et al, 2008;BRD09). For this study, the domain is centred over the southeastern regions of France and has a horizontal grid spacing of about 2.4 km (Figure 1).…”
Section: Model Set-upmentioning
confidence: 99%
See 1 more Smart Citation
“…Heavy rainfall events are characterized by mesoscale systems generating large precipitation totals that could persist for several days. The synoptic patterns leading to these events are generally well known, but the intensity and the stationarity of these systems are mainly controlled by various mesoscale factors, including the Mediterranean Sea, the surrounding mountains, cooling beneath the convection due to precipitation evaporation, low-level wind convergence and moisture transport Lionello et al, 2006;Nuissier et al, 2008). Most often, a moderate to intense low-level offshore jet, which is a governing-factor in the air-sea energy exchanges, characterizes the meteorological environment of these events.…”
Section: Introductionmentioning
confidence: 99%
“…The results of these previous studies advocate using in our study an atmospheric model able to represent Mediterranean heavy precipitation events in a realistic way, including the intensity of the heavy rainfall and the low-level jet associated with these events. The MESO-NH model (Lafore et al, 1998) used at a kilometric-scale resolution has proven its ability to capture these events quite well Lebeaupin et al, 2006;Nuissier et al, 2008) and has therefore been selected for the atmospheric component of our air-sea coupled system. In our study, MESO-NH is coupled to a one-dimensional ocean model (Gaspar et al, 1990) that has been shown to represent relatively well the vertical mixed layer structure and the SST evolution (Blanke and Delecluse, 1993;Alexander et al, 2000).…”
Section: Introductionmentioning
confidence: 99%